How much is too much? A medication use evaluation of VA ICU sedation practice during the COVID-19 pandemic - Ian C. Murphy; Kelly Bryan; Muriel Burk; Rong Jiang; Francesca Cunningham; Sarah Providence; Elizabeth Rightnour; Sarah Zavala; Kathleen Morneau; Trisha Exline; Stacey Rice; Travis Schmitt; et al. (PLoS ONE, 2025)
OBJECTIVES Early data suggested higher sedative requirements for ventilated COVID+ patients, deviating from established guidelines. We assessed the relationship between sedative use and outcomes in mechanically ventilated Veterans during the COVID-19 pandemic. Design Retrospective Medication Use Evaluation Setting National Sample of 13 Distinct VA Medical Center Intensive Care Units Patients Critically ill Veteran patients requiring mechanically ventilation for ≥2 days Interventions None. Measurements and main results The proportion of patients receiving fentanyl, midazolam and propofol was higher during COVID years. Compared with pre-COVID, median fentanyl dose was higher during Years 1 and 2 (1575mcg [(IQR) 1000–1650] vs. 1900 [1250–3000] vs. 1910 [1150–3500]). Adjuvant antipsychotics use was relatively low but tended to increase over time (pre = 10.5% vs. Year 1 = 12.3% vs. Year 2 = 14.1%). Most patients started on antipsychotics in the ICU were continued on the drug after extubation. Mortality was higher during COVID years (pre = 26.9% vs. 1 = 36.8% and 2 = 35.9%). In stratified analyses by COVID status years 1–2 (n = 79, 27%), a higher proportion of COVID+ patients received fentanyl (96% vs. 84%) and propofol (90% vs. 77%) and at higher doses (fentanyl = 1650mcg vs. 2688mcg median cumulative dose; propofol maximum infusion rate = 30 mc/kg/min (20–50) vs. 40 (25–50)). Sedative doses were similar to pre-COVID among non-COVID patients. Anti-psychotics were more frequently continued post extubation among COVID+ (34.6% vs. non-COVID+=14.9%). COVID+ patients were also less likely to have awakening and breathing trials at 48 hours after intubation (18% vs. 46%). Conclusions Sedative use and dosing increased during the first two years of COVID compared to pre-COVID, especially for COVID+ patients. The sustained elevated levels of fentanyl use in Year 2 suggests possible ‘therapeutic creep’ away from guideline-concordant practices for COVID+ patients. Antipsychotic prescription during intubation and following extubation was also more common among COVID + . These findings could inform development and implementation of safer sedation practices across VA ICUs during respiratory pandemics.